Effect of Chlorides on Conductivity and Dielectric Constant in Hardened Cement Mortar: NDT for Durability Evaluation - Sunkook Kim; Joowon Kang; Sang-Hyo Lee; Yong Han Ahn (Advances in Materials Science and Engineering)
Dielectric constant and conductivity, the so-called EM properties (electromagnetic), are widely adopted for NDT (Nondestructive Technique) in order to detect damage or evaluate performance of concrete without damage to existing RC (reinforced concrete). Among deteriorating agents, chloride ion is considered as one of the most critical threats due to rapid penetration and direct effect on steel corrosion. In the work, cement mortar samples with 3 w/c (water-to-cement) ratios and 4 levels of chloride addition are considered. Conductivity and dielectric constant are measured in the normal frequency range. They increase with strength of mortar and more chloride ions due to denser pore formation. Furthermore, the behaviors of measured EM property are investigated with carbonation velocity and strength, which shows an attempt of application to durability evaluation through EM measurement.